ПРАВО НА ОСВІТУ ДІТЕЙ З ОСОБЛИВИМИ ОСВІТНІМИ ПОТРЕБАМ В ЗАКОНІ УКРАЇНИ «ПРО ДОШКІЛЬНУ ОСВІТУ» - Малишевська, Ірина (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті проаналізовано Закон України «Про дошкільну освіту» щодо права на рівний доступ до якісної освіти дітей дошкільного віку з особливими освітніми потребами та інвалідністю. У сучасній українській освітній системі внаслідок світових процесів глобалізації, демократизації і гуманізації, під впливом досвіду міжнародного освітнього простору відбувається модернізація освіти дітей з особливостями психофізичного розвитку у напрямі формування інклюзивної моделі їх навчання та виховання. У статті зазначено, що існуюча державна політика в галузі дошкільної освіти визначається як консервативна і побудована на засадах медичної моделі допомоги дітям з особливими освітніми потребами та інвалідністю. В статье проанализировано Закон Украины «О дошкольном образовании» относительно права на равный доступ к качественному образованию детей с особами потребностями и инвалидностью. В современной украинской образовательной системе в следствие мирових процессов глобализации, демократизации и гуманизации, под влиянием международного образовательного опыта опроисходит модернизация образования детей с особенностями психофизического развития в направлении формирования инклюзивной модели их обучения и воспитания. В статье указано, что существующая государственная политика в области дошкольного образования определяется как консервативная и построена на основе медицинской модели помощи детям с особыми образовательными потребностями и инвалидностью. The article analyses the law of Ukraine on preschool education in terms of promoting equal rights to education for children with special educational needs and disability. The world’s processes of globalization, democratization and humanization as well as international educational practice brought the Ukrainian system of education up-to-date. Updating resulted in emerging the inclusive model of education for children with special educational needs and disability. Nowadays great attention is paid to the quality of preschool education for children with special educational needs and disability. There appeared the necessity for developing government bills focusing on the creation of favorable conditions for their training, education, realization of their personal potential, socialization and adaptation in society. The article states that the national policy of Ukraine in preschool education is considered to be conservative. It is built on the basis of the medical model of care for children with special educational needs and disability. There are contradictions between conceptual principles of preschool education, incorporated in the introduction of the document, and ways and directions for their implementation. Though focused on the future, the conceptual foundations are declarative. They do not clearly define the forms of educational services based on inclusion. Thus appears the necessity for further improvement of legislation of Ukraine in preschool education.